Two Independent Pathways for Self-Recognition in Proteus mirabilis Are Linked by Type VI-Dependent Export - Larissa M. Wenren (American Society for Microbiology, 2013)
ABSTRACT Swarming colonies of the bacterium Proteus mirabilis are capable of self-recognition and territorial behavior. Swarms of independent P. mirabilis isolates can recognize each other as foreign and establish a visible boundary where they meet; in contrast, genetically identical swarms merge. The ids genes, which encode self-identity proteins, are necessary but not sufficient for this territorial behavior. Here we have identified two new gene clusters: one (idr) encodes rhs-related products, and another (tss) encodes a putative type VI secretion (T6S) apparatus. The Ids and Idr proteins function independently of each other in extracellular transport and in territorial behaviors; however, these self-recognition systems are linked via this type VI secretion system. The T6S system is required for export of select Ids and Idr proteins. Our results provide a mechanistic and physiological basis for the fundamental behaviors of self-recognition and territoriality in a bacterial model system. IMPORTANCE Our results support a model in which self-recognition in P. mirabilis is achieved by the combined action of two independent pathways linked by a shared machinery for export of encoded self-recognition elements. These proteins together form a mechanistic network for self-recognition that can serve as a foundation for examining the prevalent biological phenomena of territorial behaviors and self-recognition in a simple, bacterial model system.